2013
DOI: 10.3389/fnbeh.2013.00165
|View full text |Cite
|
Sign up to set email alerts
|

Embodying an outgroup: the role of racial bias and the effect of multisensory processing in somatosensory remapping

Abstract: We come to understand other people's physical and mental states by re-mapping their bodily states onto our sensorimotor system. This process, also called somatosensory resonance, is an essential ability for social cognition and is stronger when observing ingroup than outgroup members. Here we investigated, first, whether implicit racial bias constrains somatosensory resonance, and second, whether increasing the ingroup/outgroup perceived physical similarity results in an increase in the somatosensory resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
6
40
2
Order By: Relevance
“…This result supports previous research by showing that it is possible to enface other-race faces (Bufalari et al, 2014;Fini et al, 2013). As in Experiment 1, however, we also did not find an effect of SMS or the subjective embodiment experience on implicit or explicit racial prejudice.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This result supports previous research by showing that it is possible to enface other-race faces (Bufalari et al, 2014;Fini et al, 2013). As in Experiment 1, however, we also did not find an effect of SMS or the subjective embodiment experience on implicit or explicit racial prejudice.…”
Section: Discussionsupporting
confidence: 80%
“…Observers' scores in the enfacement questionnaire indicated a persistent subjective enfacement effect after SMS that was evident in seven out of eight items. This result supports previous research, by showing that it is possible to enface other-race faces (Bufalari et al, 2014;Fini et al, 2013). However, we did not find an effect of SMS on racial prejudice, both when this was measured with the IAT and the racial prejudice scale.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Fini, Cardini, Tajadura-Jiménez, Serino, and Tsakiris (2013) found that synchronous touch on one's own face and that of a racial out-group member served to eliminate in-group bias in the extent to which we ''resonate'' with other people's tactile experiences (the ''visual remapping of touch'' effect). Furthermore, this change was mediated by participant's pre-existing implicit racial bias, with the greatest change occurring for those with the most bias.…”
Section: Embodimentmentioning
confidence: 99%